2020
DOI: 10.15294/kemas.v16i2.22895
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Quality of Life in The Elderly: WHOQOL-BREF and WHOQOL-OLD Indonesian Version

Abstract: In Indonesia, the elderly are someone who has reached the age of 60 years old and over. Along with the aging, there will be changes in sleep pattern and awakening process so that insomnia will appear. Insomnia can cause decrease in quality of life. The aim of this study was to analyze the relationship between insomnia and quality of life in elderly which measured by WHOQOL-BREF and WHOQOL-OLD Indonesian version. The quantitative analytical cross-sectional study had been carried out to 60 elderly from 6 public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The QOL in this study population in terms of the WHOQOL-BREF was considerably higher than in a similar Polish sample (‘Physical Health’: 57.9 vs. 50.9, ‘Psychological’: 66.0 vs. 59.2, ‘Social Relationships’: 68.1 vs. 54.8, ‘Environment’: 70.9 vs. 58.5) [ 66 ]. Unfortunately, the majority of previous studies using the WHOQOL questionnaires included subjects aged 60 years and older, hampering a comparison with this study’s sample [ 47 , 62 , 130 , 131 ]. The same applies to the German reference data from the WHOQOL-OLD manual [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…The QOL in this study population in terms of the WHOQOL-BREF was considerably higher than in a similar Polish sample (‘Physical Health’: 57.9 vs. 50.9, ‘Psychological’: 66.0 vs. 59.2, ‘Social Relationships’: 68.1 vs. 54.8, ‘Environment’: 70.9 vs. 58.5) [ 66 ]. Unfortunately, the majority of previous studies using the WHOQOL questionnaires included subjects aged 60 years and older, hampering a comparison with this study’s sample [ 47 , 62 , 130 , 131 ]. The same applies to the German reference data from the WHOQOL-OLD manual [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio comparativo realizado en Brasil con 600 personas adultas mayores se evidenció que la fiabilidad del WHOQOL-OLD en su versión original oscilaba entre 0.50 a 0.70 y en su versión reducida oscilaba de 0.52 a 0.77 presentando un mejor ajuste y menor probabilidad de error (De Melo et al, 2018), dentro de un estudio con 120 adultos mayores mexicanos determinaron que el alpha de Cronbach para la versión en español fue de 0.89 y para una muestra de 794 personas de 60 a 89 años, su consistencia interna total alcanzó los 0.84, demostrando ser una herramienta útil dentro de población hispanohablante (Hernández-Navor et al, 2015;Quiroz et al, 2013), en otro estudio con 921 adultos mayores de Portugal la consistencia interna del WHOQOL-OLD tanto en su versión original como en la versión portuguesa europea demostraron excelentes parámetros de fiabilidad y validez (Vilar, Sousa & Simões, 2016); centros de salud pública, residencias de ancianos e investigadores utilizan esta herramienta para medir la calidad de vida de sus adultos mayores en diferentes escenarios y culturas (Bangun, Gondodiputro & Andayani, 2020;Leles da Costa Dias et al, 2019;Amonkar et al, 2018).…”
Section: Cuestionario Whoqol-oldunclassified
“…3 According to the World Health Organization (WHO), the QOL could be assessed by person's perception of their position in life, in the context of culture and values in their surrounding environment, as well as with the goals, expectations, standards, and attention of each individu. 15 There are several instruments of QOL assessment, such as World Health Organization Quality of Life (WHOQOL)-100, WHOQOL-BREF, and WHOQOL-OLD. 15 The WHOQOL is a simple instrument and can be evaluated in all ages.…”
Section: Introductionmentioning
confidence: 99%
“…15 There are several instruments of QOL assessment, such as World Health Organization Quality of Life (WHOQOL)-100, WHOQOL-BREF, and WHOQOL-OLD. 15 The WHOQOL is a simple instrument and can be evaluated in all ages. The study of the QOL of the elderly using the WHOQOL-BREF conducted in Indonesia showed that most of the elderly had low quality of life scores on several aspects of each domain, consisting of energy adequacy, ability to carry out ADL, satisfaction with physical capacity, ability to work, ability to concentrate, acceptance of physical appearance, satisfaction with sex life, financially sufficient, information availability, recreational activities, and transportation.…”
Section: Introductionmentioning
confidence: 99%